Alcune congetture ai commenti di Proclo al Timeo e all’Alcibiade Primo - Luci, Laura (Lexis, 2025)
This paper aims to put forward four conjectures at controversial passages from Proclus’ commentaries on the Alcibiades I and on the Timaeus.